The University of Belize strategy for coping with COVID-19 - Thompson, Cindy (MUMA College of Business | University of South Florida, 2021)
The national university of Belize was forced to close its door on March 20, 2020, due to the deadly pandemic, COVID-19. Its president, Professor Clement Sankat was faced with the challenging decision of how to meet the goals of the university via an electronic means. The president’s decisions revolved around developing a strategic plan for the way forward--both to complete the semester and to plan for the start of a new semester in the fall of 2020.
Keywords: University of Belize; Covid-19